Cloud fraction mediates the aerosol optical depth - cloud top height relationship - Gryspeerdt, E; Stier, P; Grandey, B (Blackwell Publishing Ltd, 2014)
The observed strong link between aerosol optical depth (τ) and cloud top pressure (ptop) has frequently been interpreted as the invigoration of convective clouds by aerosol, with increased τ being strongly correlated with decreases in ptop (increases in cloud top height). A strong correlation between τ and cloud fraction (fc) has also been observed. Using satellite-retrieved data, here we show that ptop is also strongly correlated to fc, and when combined with the strong sensitivity between fc and τ, a large proportion of the relationship between ptop and τcan be reconstructed. Given the uncertainties about the influence of aerosol-cloud interactions on the τ-fc relationship, this suggests that a large fraction of the τ-ptop correlation may not be due to aerosol effects. Influences such as aerosol humidification and meteorology play an important role and should therefore be considered in studies of aerosol-cloud interactions.